Analgesic, Anti-diarrheal, CNS-depressant, Membrane Stabilizing and Cytotoxic Activities of Canavalia virosa (Roxb.) W&A (Bangladesh Pharmaceutical Journal, 2019)
The methanol extract of the leaves of Canavalia virosa (Roxb.) W&A was investigated for the evaluation of analgesic, anti-diarrheal and CNS-depressant activities in Swiss albino mice. The analgesic activity was assessed by formalin-induced paw licking method, where the crude extract of C. virosa (400 mg/kg, b.w.) exhibited 41.46% reduction of licking response in mice as compared to 73.17% reduction exhibited by standard acetylsalicylic acid. In the castor oil-induced diarrhea in mice, the plant extract at the dose of 200 mg/kg, b.w., demonstrated 56% reduction of diarrheal feces in mice, while the standard loperamide revealed 76% reduction of diarrheal feces. The CNS-depressant activity of the plant extract was assessed through phenobarbitone-Na induced sleeping time test. The methanol extract of C. virosa and its different Kupchan fractions were also subjected to screen membrane stabilizing and cytotoxic activities using acetylsalicylic acid and vincristine sulphate as standard, respectively.Bangladesh Pharmaceutical Journal 22(2): 214-218, 2019